2000
DOI: 10.1152/physiolgenomics.2000.4.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of skeletal muscle from transgenic animals with upregulated heat shock protein 70

Abstract: The influence of inducible heat stress proteins on protecting contracting skeletal muscle against fatigue-induced injury was investigated. A line of transgenic mice overexpressing the inducible form of the 72-kDa heat shock protein (HSP72) in skeletal muscles was used. We examined the relationship between muscle contractility and levels of the constitutive (HSC73) and inducible (HSP72) forms of the 72-kDa heat shock protein in intact, mouse extensor digitorum longus (EDL), soleus (SOL), and the diaphragm (DPH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…It has also been reported that DOX-generated ROS induce apoptosis by activating p38 MAPKs subunits ␣ and ␤. Interestingly, heat shock proteins (HSPs), which are induced in response to stress, have been found to be phosphorylated by the MAPK-assisted protein kinase 2 (MAPKAP-2, downstream of p38 MAPK), and the phosphorylated HSPs can act as negative regulators of apoptosis (5, 6), suggesting that induction of HSPs should regulate the p38 MAPK and, possibly, inhibit DOX-induced apoptosis, although this novel hypothesis remains untested.Cardioprotection by small HSPs against ischemia-reperfusion injury and other oxidative stresses has been investigated recently (23,33,37,40). Specifically, HSP27 and its murine homolog HSP25 have been shown to play important roles in…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that DOX-generated ROS induce apoptosis by activating p38 MAPKs subunits ␣ and ␤. Interestingly, heat shock proteins (HSPs), which are induced in response to stress, have been found to be phosphorylated by the MAPK-assisted protein kinase 2 (MAPKAP-2, downstream of p38 MAPK), and the phosphorylated HSPs can act as negative regulators of apoptosis (5, 6), suggesting that induction of HSPs should regulate the p38 MAPK and, possibly, inhibit DOX-induced apoptosis, although this novel hypothesis remains untested.Cardioprotection by small HSPs against ischemia-reperfusion injury and other oxidative stresses has been investigated recently (23,33,37,40). Specifically, HSP27 and its murine homolog HSP25 have been shown to play important roles in…”
mentioning
confidence: 99%
“…Cardioprotection by small HSPs against ischemia-reperfusion injury and other oxidative stresses has been investigated recently (23,33,37,40). Specifically, HSP27 and its murine homolog HSP25 have been shown to play important roles in…”
mentioning
confidence: 99%
“…It has been observed that overexpression of HSP72 suppresses expression of HSC70 (18,24). Thus one possible explanation of the findings is that the overexpressed HSP72 inhibits the expression of HSC70 and then replaces it in key functions in the normal, noninjured cell.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also showed no protection to contracting skeletal muscles (Nosek et al 2000). However, more recent studies suggest that HSPs may be beneficial to skeletal muscle under certain conditions of stress (McArdle et al 2004;Kayani et al 2008;Touchberry et al 2012;Liu et al 2013).…”
Section: Introductionmentioning
confidence: 97%